Pengaruh Literasi Keuangan, Gaya Hidup dan Teman Sebaya terhadap Perilaku Keuangan Mahasiswa Universitas Sarjanawiyata Tamansiswa - Silvia Cresya Rajagukguk; Pristin Prima Sari (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This research aims to examine the relationship between financial literacy, lifestyle and peers to student financial behavior and to find out the difference in financial literacy, lifestyle and peers to the financial behavior of students majoring in management of the faculty of economics. The type of research used is descriptive quantitative research and primary data with data collection techniques using questionnaires. The sample used amounted to 67 students consisting of students majoring in the department of economics faculty of Sarjanawiyata Tamansiswa University, this study used judgement sampling. This study shows financial literacy has a significant effect on student financial behavior, lifestyle has a significant effect on student financial behavior, peers have a significant effect on student financial behavior and financial literacy, lifestyle and peers have a significant effect on student financial behavior. In conclusion, if the financial literacy of students majoring in management is good then they can manage or manage finances well so that they are free from high lifestyle and not affected by negative things from peers. Keywords: Financial Literacy, Lifestyle, Peers, Financial Behavior